Correlation of Junk Food, Genetic Factor, and Menarche Age with Fibroadenoma Mammae at Surgery Policlinic Rantauprapat General Hospital, Labuhanbatu - Siregar, Andi Putra; Zuska, Fikarwin Zuska; Sinaga, Taruli Rohana (Sari Mutiara Indonesia University Press, 2018)
There are many risk factors which have an act to distribute Fibroadenoma mammae (FAM) to the women such as junk food consumption factors, genetic factors, and the women who gets the menstruation in age less than 12 years old. In RSUD Rantauprapat, the scores of FAM are increasing in every year. In 2014, the researcher found 202 (27,83%) cases of FAM. Therefore, the cases increased as many as 233 (28,36%) cases in 2015. In 2016, the cases increased too as many as 298 cases (30,52%). This research aims to determine the relation between junk food consumption, genetic factors, and age of menarche with Fibroadenoma mammae cases at surgical polyclinic of RSUD Rantauprapat. The design of this research was analytic design which used case control and the researcher did the data analysis as univariate, bivariate, and multivariate. The result of this research showed us the relation between junk food consumption (p value = <0,015), genetic factors (p value = <0,040), and age of menarche (p value = <0,031). Therefore based on the result of research, the researcher found the genetic factors were the most related factors to FAM cases that were (p = 0,001; OR = 0,005). In this thesis, the researcher wishes all of the women regulate their dietary habit especially to the women who come from a family that has FAM historic disease and the women who gets the menstruation cycle in age less than 12 years old.